APLICACIÓN DEL CAD/CAM EN LA PLANTA PILOTO DE CONFECCIONES DE PRENDAS DE VESTIR DE LA Fll - UNMSM - Rojas Lazo, Oswaldo (1999)
This paper presents a CAD / CAM system used in apparel garment, the advantages over the traditional system and the possibility of gradually implemented in the pilot plant confection of Fll - San Marcos.